(untitled) (Scientific journal of the Fergana State University, 2024)
Philosophy and science of the X-XII centuries. fundamentally different from the science of previous eras. The most famous directions of philosophical thought of the Middle Ages were the philosophical and religious-philosophical schools of Eastern Peripatetism, Ismailism, Sufism and especially Kalam. Discussions between them, as well as within these movements, between their individual major representatives, contributed to the development of philosophical ideas. An adequate understanding of the philosophy of the Mutakallims is necessary, first of all, for a correct understanding of its place in spiritual life with all the diversity of its constituent ideological movements and schools - Kalam, Sufism, Peripatetism, Ismailism, etc. The purpose, study and research of the “Kalam” movement shows that it practice gave a foundation to consciousness, and it acquired methodological weapons that strengthened the capabilities of the mind. The theoretical and philosophical teachings of Islam became the basis for the subsequent development of progressive philosophical thoughts. This particular contribution occupies a central place in the philosophy of the medieval Islamic world.